An experimental evaluation of the impact of the EDoS attacks against cloud computing services using AWS - Bulla, Suneetha; Basaveswara Rao, B.; Gangadhara Rao, K.; Chandan, K. (International Journal of Engineering and Technology, 2017)
Cloud computing is that the one among the quickest making and rising development in IT trade on pay-as – you-go premise. Flexibility is that the one among the properties of the cloud computing, it exhibits the response for DDoS ambush and created new quite strike significantly EDoS assault .This paper displays the impact of EDoS assaults on the cloud computing services, touching on single category of service. A check demonstrate was made public, performed associated contrasted and an expositive lining model. The trial test-bed was directed on Amazon internet Services cloud platform, it catches the cloud edges and incorporates range of execution measurements and value measurements, as an instance, range of running cases on the cloud, latency or latency , usage of distributed computing assets, throughput, and also the caused value as a result of the assault. The outcomes square measure introduced and conclusions square measure talked concerning.